VD_FINDINFO AI 294/13 - 108/2015 vom 29. April 2015 - VD Tribunal cantonal (2015)
DEGRÉ DE L'INVALIDITÉ, ATTEINTE À LA SANTÉ PHYSIQUE, ATTEINTE À LA SANTÉ PSYCHIQUE | 28 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 LPGA